The role of social media in building shopping value, customer trust, and customer engagement - Siti Zuhra Handayani; Astri Yuza Sari (Universitas Negeri Padang, 2022)
This paper aims to determine the role of Instagram live streaming in building shopping value and customer trust towards customer engagement in Padang Makeup Store Consumers in Padang City. The sample in study are 170 consumers in Padang society. Data processed using Smart PLS 3.0. The result of this research are: (1) utilitarian value has a positive effect on customer trust at the Padang makeup store, (2) hedonic value has a positive effect on customer trust at the Padang makeup store, (3) utilitarian value has a positive effect on customer engagement at the Padang makeup store, (4) hedonic value has a positive effect on customer engagement at the Padang makeup store, (5) customer trust has a positive effect on customer engagement at the Padang makeup store, (6) utilitarian value has a positive effect on customer engagement through customer trust at the Padang makeup store, (7) hedonic value has a positive effect on customer engagement through customer trust at the Padang makeup store.